Academic freedom in primary and secondary school teaching. (July 2019) - Maxwell, Bruce; Waddington, David I.; McDonough, Kevin
Why do society and the courts so readily recognize university and college teachers' academic freedom but just as readily deny primary and secondary school teachers the same right? To investigate this question, this article considers teachers' work in light of the standard justifications for granting academic freedom in higher education: that academic freedom is essential to promoting the capacity for critical reflection and the reliable transfer of disciplinary knowledge. Considering that society calls on teachers to play a key role in advancing both of these educational and social goods, the article argues that granting academic freedom in higher education, while denying it for primary and secondary teachers, appears to be a double standard. The claims to academic freedom typically reserved for university professors, we show, also apply to the work of primary and secondary teachers. There are significant differences between teaching in the higher education sector as opposed to the compulsory education sector. School teachers work with a conscripted clientele of minors and are therefore rightly subject to more stringent norms of public accountability. These differences notwithstanding, the concept of academic freedom, the article concludes, is a potentially powerful source of leverage for addressing concerns about the erosion of teachers' professional autonomy and for increased teacher involvement in the elaboration and management of the regulatory frameworks that govern their work.